Pengaruh Metode Komunikasi SBAR terhadap Kepuasan Pasien: Literature Review - Fadilah, Ana; Hidayat, Muhammad Syahid (LPPM UNIKAL, 2024)
Ineffective communication between the medical team, especially nurses and doctors, can lead to medical errors that impact patient satisfaction. The SBAR (Situation, Background, Assessment, Recommendation) communication method was introduced as an effective way to improve communication in the healthcare environment. This study aims to analyze the effect of implementing the SBAR communication method on patient satisfaction through a literature review. The technique used was a literature review that followed the PRISMA guidelines. Articles were retrieved from Pubmed, Google Scholar, and Science Direct databases, and published between 2019 and 2024. Of the 29,400 articles found, filtering was carried out until 25 articles that met the criteria were left, using an analysis of the PRISMA guide. The results showed that the implementation of SBAR significantly improved the clarity and quality of communication between medical personnel, reduced misinformation, and contributed to improved patient safety. In surgical and palliative care, SBAR was shown to speed up decision-making and improve patient satisfaction. However, several studies have revealed that SBAR is considered too rigid in emergencies that require flexibility and rapid response, and less effective in complex cases. Other challenges include inconsistent adoption in busy hospitals and the need for ongoing training to maintain effective use of SBAR. Despite implementation challenges, SBAR remains an important communication tool to improve patient safety and satisfaction, especially in clinical environments requiring clear and structured information transfer.